The Content and Sequencing Analysis of English for Office Skills Program in Vocational and Education Training Center in Pekalongan - Pranesti, Dian; Kurniawati, Ayu; Nurhayati, Nurhayati (PAROLE: Journal of Linguistics and Education, 2017)
English for Office Skills is one of the programs that is held by Balai Latihan Kerja (BLK) or Vocational and Education Training Center (VETC) in Pekalongan Regency. The program is done to answer the need of the participants for English communication skill in the workplace. The needs analysis in this article is needed to see the necessity of such skill for the job-seekers. It also examines whether the program has become the answer for their necessity. The needs analysis also helps the teacher and institution to develop a better strategy in content and sequencing so that the program that is done in limited time can be organized effectively. In this case, the data is collected through the questionnaire and interview. The quantitative and descriptive qualitative method is done to analyze the data. The result shows that the speaking skill is the most important skill needed by the participants. According to this need, the teacher can develop a strategy in making the effective syllabus and lesson plan so that the program can be completed well although in a limited time.Â